Ideological radicalism and democratic experience in new democracies. Issue 4 (6th June 2016) - Jou, Willy
Abstract : In comparing publics' ideological self-placements between established and new democracies, it has been observed that there is a higher proportion of citizens who express radical views in the latter countries. This is likely due to sharp differences with regard to evaluations of past authoritarian rule, the legitimacy of the new regime, or new institutional arrangements governing the distribution of power when countries embark on democratic transition. Studies on the attitudinal aspect of democratic consolidation lead one to expect a decrease in extreme views in new democracies with the passage of time, as questions of regime principles and institutions are settled, and citizens come to accept democracy as the "only game in town". The present article investigates whether this proposition is applicable to "Third Wave" new democracies in Eastern Europe, Latin America, and East Asia by examining longitudinal public opinion data from 23 countries. In addition to the length of democratic regimes, We also analyse the impact of economic performance, quality of governance, and electoral systems on the proportion of radical citizens. Results show that while longer democratic experience does contribute to reducing extremist leanings, factors such as the level of corruption, rule of law, and plurality electoral rules play a more substantive role.